Implementation of Smart City Development Policy in Bandung City, Indonesia - Ika Widiastuti; Nany Suryawati (LPPM of NAROTAMA UNIVERSITY, 2021)
Purpose: Traffic congestion problems that occur in Bandung, Indonesia are suspected to be implemented using technology and information-based transportation system Smart City. Smart cities in several countries can overcome problems in the fields of economy, health, education, governance, transportation, and the environment. This research is designed to describe the implementation of smart city development policies in the city of Bandung. Design/methodology/approach: This study uses qualitative. The object of this research is the implementation of smart city development policies implemented in the city of Bandung, Indonesia. The subjects of the study were Bandung City, Indonesia Transportation Department employees. Data collection techniques using the method of observation, interviews, and documentation. Data analysis techniques using data reduction, data presentation, and conclusion. Findings: The results showed that: (1) Bandung city government website contains information about the city of Bandung, government, tourism, education, investment, maps, articles, prayer schedules, and weather forecasts. (2) Online public services for the aspirations and complaints of the people of Bandung. (3) RW Net services in the city of Bandung. BIRMS (Bandung Integrated Resource Management System) is an online public service in the form of integrated information, which is supported to help manage government resources. (2) Online public services for the aspirations and complaints of the people of Bandung. (3) RW Net services in the city of Bandung. BIRMS (Bandung Integrated Resource Management System) is an online public service in the form of integrated information, which is supported to help manage government resources. (2) Online public services for the aspirations and complaints of the people of Bandung. (3) RW Net services in the city of Bandung. BIRMS (Bandung Integrated Resource Management System) is an online public service in the form of integrated information, which is supported to help manage government resources. Research limitations/implications: Results of this research can be used as references in implementing the smart city concept in other cities in Indonesia. Practical implications: The use of technology is the key to implementing smart city policies in a city. The technology used does not have a negative impact on the environment, the technology is innovative and sustainable, is aware of the environment. Smart City is used to represent the ability of a city in providing services to the community by providing the information needed about the city Originality/value: This research is original. Paper type: Research paper